2017
DOI: 10.1371/journal.pone.0172560
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine treatment outcomes among gay men attending a LGBTI-specific treatment service in Sydney, Australia

Abstract: Gay and bisexual men (GBM) report higher rates of methamphetamine use compared to heterosexual men, and thus have a heightened risk of developing problems from their use. We examined treatment outcomes among GBM clients receiving outpatient counseling at a lesbian, gay, bisexual, transgender and intersex (LGBTI)-specific, harm reduction treatment service in Sydney, Australia. GBM receiving treatment for methamphetamine use from ACON’s Substance Support Service between 2012–15 (n = 101) were interviewed at trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Much of the intervention work for methamphetamine-using MSM has focused on therapeutic or individual-level interventions that rely on cognitive behavioral therapy, often with motivational interviewing or contingency management. Research has demonstrated the effectiveness of this approach (Rawson et al 2004; Zule et al 2012; Reeback et al 2014; Lea et al 2017). However, it is likely that men in the minimal and marijuana PSU classifications and perhaps some men in the other classifications are functional users who are not actively seeking therapeutic, detoxification, or treatment services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the intervention work for methamphetamine-using MSM has focused on therapeutic or individual-level interventions that rely on cognitive behavioral therapy, often with motivational interviewing or contingency management. Research has demonstrated the effectiveness of this approach (Rawson et al 2004; Zule et al 2012; Reeback et al 2014; Lea et al 2017). However, it is likely that men in the minimal and marijuana PSU classifications and perhaps some men in the other classifications are functional users who are not actively seeking therapeutic, detoxification, or treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. National HIV/AIDS Strategy highlights the importance of substance use prevention and treatment as a critical component in reducing HIV incidence in the United States (ONAP, 2016). Substance use prevention and treatment interventions have found success in combining motivational interviewing or contingency management with cognitive behavioral therapy to reduce risk behavior (Avants et al 2004; Rawson et al 2004; Shoptaw et al 2005; Schumacher et al 2007; Garfein et al 2010; Lim et al 2015; Rice, 2016; Lea et al 2017). Motivational interviewing aims to increase awareness of the consequences and risk associated with behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence around how methamphetamine use affects HRQOL is limited. Several studies report changes in HRQOL as part of the economic evaluations of treatment , but few studies report quality of life utility values for people who use methamphetamine , or examine what factors are associated with poor quality of life . What can be gleaned from this small body of research is that people who use the drug have a poor quality of life, especially poorer mental health than the general population , and that this related to their demographic status, psychiatric history as well as their severity of drug use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for methamphetamine users in general (regardless of gender or sexual identity), as well as interventions tailored towards GBM, have produced improvements in various outcomes (e.g., reductions in methamphetamine use and/or in sexual risk behavior). These interventions have utilized a range of approaches: cognitive behavioral therapy (CBT) combined with contingency management [30], which was expanded to include sexual risk reduction intervention and gay-specific social support therapy [31]; a Matrix or manualized treatment model [32]; contingency management [33]; motivational interviewing (MI) combined with CBT [34]; behavioral activation combined with risk reduction counseling [35]; a single session of MI [36]; text-messaging [37]; and acceptance and commitment therapy combined with CBT and MI [38]. A 7-session couples-based approach was also effective in reducing use and sexual risk among Black GBM couples [39].…”
Section: Introductionmentioning
confidence: 99%